A Prospective, Longitudinal Magnetic Resonance Imaging Evaluation of Cerebrovascular Reactivity and Infarct Development in Patients With Intracranial Stenosis. Issue 3 (24th March 2021) - Juttukonda, Meher R.; Davis, Larry T.; Lants, Sarah K.; Waddle, Spencer L.; Lee, Chelsea A.; Patel, Niral J.; Jordan, Lori C.; Donahue, Manus J.
Abstract : Background: Patients with symptomatic atherosclerotic and non‐atherosclerotic (i.e., moyamoya) intracranial steno‐occlusive disease experience high 2‐year infarct rates. Purpose: To investigate whether cerebral blood flow (CBF) and cerebrovascular reactivity (CVR) measures may provide biomarkers of 1‐to‐2‐year infarct risk. Study Type: Prospective, longitudinal study. Subjects: Adult participants (age = 18–85 years) with symptomatic intracranial atherosclerotic disease ( N = 26) or non‐atherosclerotic (i.e., moyamoya; N = 43) and stenosis ≥50% of a major intracranial artery were initially scanned within 45 days of stroke. Follow‐up imaging (target = 1.5 years) was acquired for new infarct assessment. Field Strength/Sequence: 3.0 Tesla with normocapnic arterial spin labeling (ASL) and blood oxygenation level‐dependent (BOLD) imaging acquired during an interleaved hypercapnic (3 minutes) and normocapnic (3 minutes) respiratory stimulus. Assessment: CBF, maximum CVR, and time‐to‐maximum CVR (i.e., CVRDELAY ) were calculated. Laterality indices (difference between infarcted and contralesional hemispheres divided by sum of absolute values) of metrics at enrollment were contrasted between participants with vs. without new infarcts on follow‐up. Statistical Tests: Laterality indices were compared using non‐parametric Wilcoxon tests (significance: two‐sided P < 0.05) and effect sizes as Cohen's d . Continuous variables are presented as mean ± SD. Results: New infarcts were observed on follow‐up in 15.0% of participants. The laterality index of the CVRDELAY was elevated ( P = 0.01) in participants with atherosclerosis with new infarcts (index = 0.13) compared to participants without new infarcts (index = 0.05). Data Conclusion: Elevated CVRDELAY may indicate brain parenchyma at increased risk for new infarcts in patients with symptomatic intracranial atherosclerotic disease treated with standard‐of‐care medical management. Level of Evidence: 2 Technical Efficacy Stage: 3